Keanekaragaman Ikan pada Ekosistem Padang Lamun di Pantai Pandaratan, Kecamatan Sarudik, Kabupaten Tapanuli Tengah, Provinsi Sumatera Utara - Huwilda Inrika; Amanatul Fadhilah (AQUACOASTMARINE, 2018)
This research aims to know the diversity of fish in seagrass at Padaratan Beach. This research was conducted in Pandaratan Beach, Sarudik Subdistrict, Central Tapanuli Regency from March until April 2018. Gill net is instrument to catch the fish at three determined stations. The diversity of fish can be assessed by looking the composition of fish species and index of diversity. The results of this study show 196 individuals, consist of 12 families and 14 species. The highest number of fish spesies at station II with total catch of 70 individuals. The most dominating fish species at all of stations is Zenarchopterus gilli with value of relative abundance in first station 22,96%, second station 20,01% and the last station 23,07%. The value of diversity index (H’) of all stations can be categorized in medium class of which score between 2,367-2,439. The value of equalibility index of all stations can be categorized in stable class of which score between 0,897-0,903, while for the value of domination index of all stations can be categorized in low class of which score between 0,102-0,127.Keywords ; Fish, Seagrass, Abundance, Diversity, Pandaratan Beach